Oral health status of residents of Brgy. Malayak, Mogpog, Marinduque - Arevalo, Jr., Glyne M.
This study aimed to determine the oral health status of residents of Brgy. Malayak, Mogpog, Marinduque, as well as the oral hygiene practices, oral health knowledge, diet habits and socio-economic profile of the population. Three age groups were included namely 12, 15-19 and 35-44 years old. Oral examination was done to determine the DMFT and OHI-S scores. Interviews of the subjects and ocular observation of their environment were also conducted. Results showed that the average DMFT of the given age groups were 2.33, 5.75 and 5.0 while OHI-S scores were 1.78, 1.44 and 1.98 respectively. A large number of subjects claim to brush their teeth twice or thrice a day with the use of toothpaste and toothbrush. With the knowledge that sweets cause tooth decay, this is avoided by age groups 12 and 35-44 years old. Majority of the subjects only know extraction as the service offered by dentist. Generally, subjects belong to the middle and lower classes of society. The oral health status of residents of Brgy. Malayak, Mogpog, Marinduque is good, based on their low DMFT (2.33, 5.75 and 5.0) and OHI-S valuesd.78. 1.44 and 1.98).